The perspectives of South African academics within the disciplines of health sciences regarding telehealth and its potential inclusion in student training - S Govender; M Mars (South African Medical Association, 2018)
The professional training and development of healthcare professionals in the area of telehealth is important to ensure the sustainability of this service delivery model. Tertiary institutions are among the key constituents involved in telehealth education, training and development. Academics within the healthcare sciences should therefore have the necessary experience and knowledge in this area to support the education and training of students. The objectives of this study were to determine the perspectives, experiences and attitudes of South African academics within various disciplines of health sciences regarding telehealth, as well as their views on suitable content areas for a telehealth module. A descriptive survey design was implemented. Sixty-six fulltime employed academic staff from five universities participated. The majority of participants were familiar with the terms telehealth/electronic health (eHealth), while 59% were unfamiliar with terms such as synchronous and asynchronous services. Eighty percent of respondents felt it necessary to include telehealth in the curriculum. The majority (89%) did not conduct research in telehealth. Seventy-one percent felt positive that telehealth could benefit the profession, and 30% stated that lack of standards creates a negative attitude toward the area and its sustainability. The majority of participants (77%) felt that their final-year students knew very little about telehealth upon exiting their study programme. Almost half (45%) of the participants felt that ethical issues were the most important aspect that needed to be included in a telehealth module, while data management was ranked as being least important (49%). The correlation between the perspectives on ethical issues and limitations to telehealth was statistically significant (p=0.007), implying that participants saw lack of ethical considerations as a limitation to the uptake of telehealth practice. While attitudes regarding telehealth were positive, concerns were raised around the lack of standards and guidelines. Opportunities for professional development in telehealth need to be created through continued professional development (CPD) workshops and training. This in turn may provide more skilled faculty to teach in this area, allowing students to receive better instruction on telehealth service delivery models.